PERAN GURU DALAM MENINGKATKAN KECERDASAN SPIRITUAL ANAK USIA 4-5 TAHUN DI PAUD BINA ANAK SHOLIH PONTIANAK SELATAN - Saleha, Risti; Ali, Muhamad; Miranda, Dian (Universitas Tanjungpura, 2023)
Teachers play an important role in developing children's spiritual quotient. Children who have spiritual quotient are able to respect themselves and others. Teachers play an important role in increasing children's spiritual quotient because teachers deal directly with students in class through the teaching and learning process. This study aims to describe the role of teachers in increasing the spiritual quotient of children aged 4-5 years in PAUD Bina Anak Sholih. The research method used is descriptive method with a qualitative research form. The subjects in the study were teachers of class A PAUD Bina Anak Sholih Pontianak Selatan. The research location is in PAUD Bina Anak Sholih Pontianak Selatan. Data collection techniques used in this study are observation, interviews, and documentation. The results of the study show that: 1. The teacher's role as a guide in improving children's spiritual quotient, the teacher always directs, supervises, and guides every activity inside and outside the classroom so that children understand religious values and children are able to apply them themselves, 2. The role of the teacher as a motivator in improving children's spiritual quotient, namely the teacher always encourages children when children are able to answer and participate in activities well, and the teacher gives rewards for what children have done, 3. The role of the teacher as a facilitator in improving children's spiritual quotient, namely the teacher provides and provides facilities to help children improve their spiritual quotient. thus the role that the teacher has implemented to improve the spiritual quotient of children aged 4-5 years in PAUD Bina Anak Sholih Pontianak Selatan has been carried out properly .